A Comparative Study of Phospholipase A1 and Phospholipase C on Soybean Oil Degumming. (2nd November 2014) - Jiang, Xiaofei; Chang, Ming; Wang, Xiaosan; Jin, Qingzhe; Wang, Xingguo
Abstract: The degumming of crude soybean oil with phospholipase A1 (PLA1 ) and phospholipase C (PLC) was studied, and optimal conditions were obtained for each enzyme. During degumming with PLA1, more fatty acid was found in the oil than would be expected by hydrolysis of only the terminal fatty acid chains, and glycerophosphophorylcholine and glycerophosphoethanolamine were detected in the gums. These observations indicate that acyl‐migration of phospholipid fatty acids occurred during PLA1 degumming. In addition, results showed that PLA1 degumming was capable of reducing the phosphorus content in the oil to levels acceptable for physical refining (<10 mg/kg). During degumming with PLC, an increase of 1, 2‐diacylglycerol was found, as most phosphatidylcholine and phosphatidylethanolamine were hydrolyzed by this enzyme. Treatment with either enzyme slightly decreased the oxidative stability of the oil and most metals were separated with the gums fraction.